Real imaging and size values of Saccharomyces cerevisiae cells with comparable contrast tuning to two environmental scanning electron microscopy modes - TOKSOY ÖNER, EBRU (JOHN WILEY & SONS INC, 2007)
The combined application of electron microscopy (EM) is frequently used for the microstructural investigation of biological specimens and plays two important roles in the quantification and in gaining an improved understanding of biological phenomena by making use of the highest resolution capability provided by EM. The possibility of imaging wet specimens in their native states in the environmental scanning electron microscope (ESEM) at high resolution and large depth of focus in real time is discussed in this paper. It is demonstrated here that new features can be discovered by the elimination of even the least hazardous approaches in some preparation techniques, that destroy the samples. Since the analysis conditions may influence the morphology and the extreme surface sensitivity of living biological systems, the results obtained from the same cultured cell with two different ESEM modes (Lvac mode and wet mode) were compared. This offers new opportunities compared with ESEM-wet/Lvac-mode imaging, since wet-mode imaging involves a real contrast and Gives an indication of the changes in cell morphology and structure required for cell viability. In this study, wet-mode imaging was optimized using the unique ability of cell quantities for microcharacterization in situ giving very fine features of topological effects. Accordingly, the progress is reported by comparing the results of these two modes, which demonstrate interesting application details. In general, the functional comparisons have revealed that the fresh unprocessed Saccharomyces cerevisiae cells (ESEM-wet mode) were essentially unaltered with improved and minimal specimen preparation timescales, and the optimal cell viability degree was visualized and also measured quantitatively while the cell size remained unchanged with continuous images.
Keywords: environmental scanning electron microscope (ESEM); Saccharomyces cerevisiae cell lysis; morphology; ESEM wet contrast; YEAST; TEMPERATURE